Small Arms and Small Countries: Firearms and the International Security Agenda - Carla Álvarez Velasco (Íconos)
This article examines the emergence of the small arms trade on the international political agenda as a growing security threat. Employing the theoretical framework proposed by the Copenhagen School, this article argues that the issue of small arms gained traction at the international level in the context of the post-Cold War. This was due to the pressure of small countries that were engulfed in violence at the hands of non-state actors in the post-Cold War era. At the regional level in Latin America, although important sub-regional differences exist, various regional initiatives have become an important example for other nations around the globe. In actuality however the positive achievements that securitization initially promoted has decreased. The study of this case leaves us with some relevant lessons both for theoretical reflection as well as for political action.